Taxonomic notes and nomenclatural corrections in Crustacea: Isopoda (exclusive of Oniscidea) - Boyko, Christopher B. (Zootaxa, 2024)
During a review of all isopod taxa (exclusive of Oniscidea), nomenclatural and taxonomic issues were found that need correction or detailed explanation. Herein, details are provided on five unreplaced species/subspecies homonyms, corrections to authorship and/or date for six genera, two families/subfamilies and 11 species, three unavailable names for subfamilies, 22 corrections to the spelling of specific names to conform to the gender of their respective genera, two junior homonyms that are replaced, and one genus that is validated herein. The history of Ianthe Bovallius, 1881 and its numerous replacement names, Brongniartia Eights, 1833, and Ceratoserolis Brandt, 1988 are discussed, a type species is selected for Vireia Viré, 1903, and Epicepon is validated as a genus name.